gopi Jun 1st, 2005 AB + A( B + C ) + B ( B + C ) = = AB+AB+AC+BB+BC = AB+AC+B+BC = AB+AC+B(1+C) = AB+AC+BC

geekijk Profile Answers by geekijk Aug 29th, 2008 (AB+AB)+AC+BB+BC (AB)+AC+(B+BC) AB+AC+B(1+C) AB+AC+B (AB+B)+AC B+AC.this is the ans

revathi Apr 24th, 2012 AB + A( B + C ) + B ( B + C ) = AB+AB+AC+B2+BC = (2AB+B2)+AC+BC = [(A+B)2-A2]+C(A+B) = (A+B)(A+B-A2)+C = (A+B)(A+B+C-A2)

Jenitaa Adel Queen Dec 4th, 2012 AB+AB+AC+BB+BC AB+AC+B+BC AB+AC+B(1+C) AB+AC+B AB+B+AC B(A+1)+AC B+AC

Walta Napuo Jun 21st, 2020 AB + A( B + C ) + B ( B + C ) = = AB+AB+AC+BB+BC = AB+AC+B+BC = AB+AC+B(1+C) = AB+AC+BCCodec

## Simplify the expression AB + A( B + C ) + B ( B + C )?

This question is related to Cisco Interview## Related Answered Questions

## Related Open Questions